Newly proposed quantitative criteria can assess chronic atrophic gastritis via probe-based confocal laser endomicroscopy (pCLE): a pilot study - Robles-Medranda, Carlos; Puga-Tejada, Miguel; Oleas, Roberto; Baquerizo-Burgos, Jorge; Alcívar-Vásquez, Juan; Del Valle, Raquel; Cifuentes-Gordillo, Carlos; Alvarado-Escobar, Haydee; Ponce-Velez, Daniel; Ospina-Arboleda, Jesenia; Pitanga-Lukashok, Hannah (Endoscopy International Open, 2022)
Background and study aims Probe-based confocal laser endomicroscopy (pCLE) can provide high magnification to evaluate chronic atrophic gastritis (CAG), but the current pCLE criteria are qualitative and prone to variability. We aimed to propose a quantitative CAG criterion based on pCLE to distinguish non-atrophic gastritis (NAG) from CAG.Patients and methods This observational, exploratory pilot study included patients with NAG and CAG evaluated via esophagogastroduodenoscopy, pCLE, and histology. We measured the gastric glands density, gastric gland area, and inter-glandular distance during pCLE.Results Thirty-nine patients (30/39 with CAG) were included. In total, 194 glands were measured by pCLE, and 18301 were measured by histology, with a median of five glands per NAG patient and 4.5 per CAG patient; pCLE moderately correlate with histology (rho = 0.307; P = 0.087). A gland area of 1890–9105 µm2 and an inter-glandular distance of 12 to 72 µm based on the values observed in the NAG patients were considered normal. The proposed pCLE-based CAG criteria were as follows: a) glands density < 5; b) gland area < 1/16 the pCLE field area (< 1890 µm2) or > 1/4 the pCLE field area (> 9105 µm2); or c) inter-glandular distance < 12 or > 72 µm; CAG was diagnosed by the presence of at least one criterion. The proposed criteria discriminated CAG with a ranged sensitivity of 76.9 % to 92.3 %, a negative predictive value of 66.6 % to 80.0 %, and 69.6 % to 73.9% accuracy.Conclusions The proposed pCLE criteria offer an accurate quantitative measurement of CAG with high sensitivity and excellent interobserver agreement. Larger studies are needed to validate the proposed criteria.